CFD study of ship-to-bank interaction - Kim, Youngkook (2015)
Ship-to-bank interaction is a complex physical phenomenon that involves not only in the asymmetric pressure field near banks or channels but also shallow water effect. Traditionally many experimental studies were carried out in this field. As numerical method is getting popular, there were various computational approaches as well. In this study, CFD (Computational Fluid Dynamics) analysis is carried out to investigate ship-to-bank interaction. CFD analysis is also useful for finding hydrodynamic coefficients in manoeuvring mathematical model of the ship-handling simulator. For the numerical method, RANS based solvers with free surface capturing feature are used.